Eelgrass communities in southeast Alaska (eelgrass density and biomass, epiphytes, and epifauna) - Wendel Raymond; Tiffany Stephens (Knowledge Network for Biocomplexity, 2018)
Intertidal seagrass community data were collected during summertime 2017 (May-August) on western Prince of Wales Island, Alaska. The purpose of these data was to characterize the eelgrass community so that analysis of trophic interactions could be assessed along a gradient of sea otter occupation for an NSF-funded project: Apex Predators, Ecosystems, and Community Sustainability (APECS, http://apecs-ak.org/). Data were collected at 21 independent sites. At each site, the coordinates, sampling date + times, and tidal elevation were recorded. At each site, one 100 m transect was laid horizontally along a shoreline, along which data were collected in 8 quadrats. Data types include eelgrass shoot count and biomass per replicate shoots, flowering eelgrass shoot count, rhizome biomass paired with shoots, rhizome internode lengths, two-dimensional percent cover of epiphytes and macroalgae within a quadrat, biomass of epiphytes wiped from eelgrass shoots, and counts and biomass of epifauna collected from eelgrass shoots. Other datasets to support this work are also archived with KNB and are searchable using the identifier “APECS_alaska”.